The iconography of the funerary altar of Laberia Daphne (90-120 AD): a comparative study - Souza Veloso, Jaqueline (Romanitas - Revista de Estudos Grecolatinos, 2024)
In this article, we propose to analyze the visual singularities of the Laberia Daphne altar, originating from Rome between the years 90-120 AD, and compare it to other similar monuments. We believe that the analysis of the iconography of the altar, in which the female figure is depicted without hair, may raise relevant discussions, not only about the importance of female hair within the identity of Roman women, but also within the configuration and understanding of the portrayed scene. Additionally, we raise the interpretation that the substitution of hair with something resembling a crown made of leaves may indicate a representation aiming to attribute to the honoree an honor that was rarely granted to women: coronation.